2013
DOI: 10.1002/da.22165
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous Telehealth Technologies in Psychotherapy for Depression: A Meta-Analysis

Abstract: Overall, we found no evidence to suggest that the delivery of psychotherapy via synchronous telehealth modalities is less effective than nontelehealth means in reducing depression symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
87
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(100 citation statements)
references
References 62 publications
5
87
1
3
Order By: Relevance
“…Additionally, most of the existing studies included interactive psychoeducational-CBT contents, self-monitoring of different parameters and the feedback mechanisms, as well as the support given either by the mental health caregivers or by patients' peers. The support provided from patients' peers or coaches in the discussed intervention programs mostly resulted in higher rates of acceptance, engagement and retention (Nicholas et al, 2010;Todd et al, 2013Todd et al, , 2014. This is consistent with the current evidence related to the standalone online support forums and discussion groups for a wide range of mental disorders including bipolar disorder (Bauer et al, 2013;Campos et al, 2014;Highton-Williamson et al, 2014;Schielein et al, 2008).…”
Section: Current Interventionssupporting
confidence: 85%
See 1 more Smart Citation
“…Additionally, most of the existing studies included interactive psychoeducational-CBT contents, self-monitoring of different parameters and the feedback mechanisms, as well as the support given either by the mental health caregivers or by patients' peers. The support provided from patients' peers or coaches in the discussed intervention programs mostly resulted in higher rates of acceptance, engagement and retention (Nicholas et al, 2010;Todd et al, 2013Todd et al, , 2014. This is consistent with the current evidence related to the standalone online support forums and discussion groups for a wide range of mental disorders including bipolar disorder (Bauer et al, 2013;Campos et al, 2014;Highton-Williamson et al, 2014;Schielein et al, 2008).…”
Section: Current Interventionssupporting
confidence: 85%
“…videoconferencing, live-text support), which have proven to be not only feasible but also an effective face-to-face approach for a wide array of mental health disorders, and allow the access to mental healthcare services to people with limited mobility or living at remote locations. Yet, the experience with such a modality of delivering psychological interventions for bipolar disorder is limited and it still requires a trained professional for each session, which limits the main aims of new technologies such as reducing costs and associated healthcare resources (Hailey et al, 2008;Hilty et al, 2013;McGinty et al, 2006;Osenbach et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…38,80 Even among participants residing in close proximity to the coordinating site (Western Washington; n = 69), more participants chose the CBT-T versus UC randomization option (n = 17) than the CBT-IP versus UC option (n = 4). Although not statistically significant, participants in the CBT-T group received a greater number of CBT sessions than did those in the CBT-IP group.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that evaluations conducted via telepsychiatry were accurate enough to replace in-person evaluations in most cases. 11 In a more recent study, Osenbach et al 12 conducted a metaanalysis that included 14 studies of depression treatment delivered via telehealth versus in-person. No significant systematic difference in effect size was found between the two modalities, although studies that indicated the use of ''care as usual'' as the comparison group differed from those using a face-to-face comparison treatment, suggesting that ''care as usual'' was inferior to treatment delivered using telehealth technology.…”
Section: Introductionmentioning
confidence: 99%